Roles of qseC mutation in bacterial resistance against anti-lipopolysaccharide factor isoform 3 (ALFPm3) - Iyacoob Khunsri; Pinidphon Prombutara; Htut Htut Htoo; Supitcha Wanvimonsuk; Thanadon Samernate; Chindanai Pornsing; Sirinit Tharntada; Phattarunda Jaree; Vorrapon Chaikeeratisak; Kunlaya Somboonwiwat; Poochit Nonejuie (PLoS ONE, 2023)
Propelled by global climate changes, the shrimp industry has been facing tremendous losses in production due to various disease outbreaks, particularly early mortality syndrome (EMS), a disease caused by Vibrio parahaemolyticus AHPND. Not only is the use of antibiotics as EMS control agents not yet been proven successful, but the overuse and misuse of antibiotics could also worsen one of the most challenging global health issues—antimicrobial resistance. To circumvent antibiotic usage, anti-lipopolysaccharide factor isoform 3 (ALFPm3), an antimicrobial peptide (AMP) derived from the shrimp innate immune system, was proposed as an antibiotic alternative for EMS control. However, prolonged use of AMPs could also lead to bacterial cross resistance with life-saving antibiotics used in human diseases. Here, we showed that ALFPm3-resistant strains of E. coli could be induced in vitro. Genome analysis of the resistant mutants revealed multiple mutations, with the most interesting being a qseC(L299R). A study of antibiotic susceptibility profile showed that the resistant strains harboring the qseC(L299R) not only exhibited higher degree of resistance towards polymyxin antibiotics, but also produced higher biofilm under ALFPm3 stress. Lastly, a single cell death analysis revealed that, at early-log phase when biofilm is scarce, the resistant strains were less affected by ALFPm3 treatment, suggesting additional mechanisms by which qseC orchestrates to protect the bacteria from ALFPm3. Altogether, this study uncovers involvement of qseC mutation in mechanism of resistance of the bacteria against ALFPm3 paving a way for future studies on sustainable use of ALFPm3 as an EMS control agent.